Evaluation of Rapid Antigen Tests Using Nasal Samples to Diagnose SARS-CoV-2 in Symptomatic Patients - Alqahtani, Manaf; Abdulrahman, Abdulkarim; Mustafa, Fathi; Alawadhi, Abdulla I.; Alalawi, Batool; Mallah, Saad I. (Frontiers in Public Health, 2022)
Introduction The best way to mitigate an outbreak besides mass vaccination is via early detection and isolation of infected cases. As such, a rapid, cost-effective test for the early detection of COVID-19 is required. Methods The study included 4,183 mildly symptomatic patients. A nasal and nasopharyngeal sample obtained from each patient was analyzed to determine the diagnostic ability of the rapid antigen detection test (RADT, nasal swab) in comparison with the current gold-standard (RT-PCR, nasopharyngeal swab). Results The calculated sensitivity and specificity of the RADT was 82.1 and 99.1%, respectively. Kappa's coefficient of agreement between the RADT and RT-PCR was 0.859 (p < 0.001). Stratified analysis showed that the sensitivity of the RADT improved significantly when lowering the cut-off RT-PCR Ct value to 24. Conclusion Our study's results support the potential use of nasal swab RADT as a screening tool in mildly symptomatic patients, especially in patients with higher viral loads.